Role of Virechana karma in Acne Vulgaris: a case report - Lalwani, Anita; Gupta, Rajesh; Rathore, Poonam (International Research Journal of Ayurveda & Yoga, 2024)
Face is one of the most fundamental part of body which conveys a wealth of information, reflects the personality and wisdom. People who experience facial problems possess a negative self-image compared to those with normal faces. In Ayurveda texts Acne is termed as yuvan pidika was first described by Acharya Sushruta as one of the kshudra rogas. Yuvan pidika means that the disease almost takes place in young age. Acene is one of the most prevalent skin conditions affecting teenagers. It is a disease of the pilosebaceous unit. It is a very common skin disorder which can be present with inflammatory or non-inflammatory lesions. It is characterized by formation of open and closed comedons, papules, pustules nodules and cysts. In Ayurveda vitiation of kapha dosha, vata dosha and rakht dhatu lead to development of mukhadushika. Ayurveda has a great potential in the management of various skin disorder and in this article success story of the management of acene vulgaris is reported. Virechan therapy is given to the patient after Snehan karma followed by Sansarjan karma. Assessment was done after Virechan karma and after Sansarjana karma. Remarkable changes were found in various symptoms after assessment.